Effects of rootstocks and developmental time on the dynamic changes of main functional substances in ‘Orah’ (Citrus reticulata Blanco) by HPLC coupled with UV detection - Li, Shuang; Yang, Lei; Wang, Min; Chen, Yang; Yu, Jianjun; Chen, Hao; Yang, Haijian; Wang, Wu; Cai, Zhiyong; Hong, Lin (Frontiers in Plant Science, 2024)
Citrus fruit is rich in important functional constituents such as flavonoids, phenolic acids terpenes and other functional substances that play an important role for treating clinical diseases or controlling major agricultural diseases and pests. Plant secondary metabolites have become one of the most important resources of novel lead compounds, expecially young citrus fruits contain multiple functional substances. 'Orah', a type of citrus reticulata, is known for its fine appearance, productivity, delicious sweetness, late-maturing characteristics, and is widely cultivated in China. Fruit thinning and rootstock selection are commonly used agronomic measures in its production to ensure its quality and tree vigor. However, few studies have demonstrated the effects of these agronomic measures on the functional substances of 'Orah'. In this study, we used HPLC coupled with UV to detect the dynamic changes of fruit quality, 13 main flavonoids, 7 phenolic acids, 2 terpenes, synephrine and antioxidant capacity in both peel and pulp of citrus fruits grafted on four rootstocks (Red orange Citrus reticulata Blanco cv. Red tangerine, Ziyang xiangcheng Citrus junos Sieb. ex Tanaka, Trifoliate orange Poncirus trifoliata L. Raf, and Carrizo citrange Citrus sinensis Osb.×P.trifoliate Raf) at six different developmental stages (from 90 DAF to 240 DAF). The results indicated that rootstock can significantly affect the contents of functional constituents and antioxidant capacity in 'Orah'. Additionally, it was found that pruning at either 90 DAF(days after flowering) or 150 DAF produced the most favorable outcomes for extracting functional substances. We also identified rootstock 'Trifoliate orange' has the highest total soluble solids (TSS) and 'Ziyang xiangcheng' to be the optimal in terms of comprehensive sensory of fruit quality, while 'Red orange' and 'Ziyang xiangcheng' are optimal in terms of functional substance quality, and 'Red orange' excels in antioxidant capacity. Overall, the findings demonstrate the important role of rootstocks and developmental stage in shaping fruit sensory quality and functional substance synthesis, providing valuable insights for guiding rootstock selection, determining thinning time, and utilizating pruned fruits in a more informed manner.